IT Capability, Audit Risk and the Role of Internal Control - Wilamsari, Feni; Rahmadhany, Umi; Musriati, Titik (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2023)
Technology investment is important for a company, especially in the era of the industrial revolution 4.0 and 5.0. which both emphasize the importance of utilizing information technology and its users to increase competitive advantage. Optimum utilization of information technology will have an impact on reducing audit risk through the effectiveness of the internal control function. This study aims to analyze whether information technology capabilities affect audit risk and internal control quality in banking companies listed on the IDX during the 2019-2022 observation. The data sources used in this analysis use secondary data sourced from financial reports and annual reports of banking companies. Samples were selected based on predetermined criteria. The data analysis technique is panel data using Eviews 9. The test results show that 1) Information technology investment has a significant effect on audit risk, 2) Internal control moderates the effect of information technology investment on audit risk. 3) ROA as a control variable has no influence on audit risk.